Penerapan Gim Edukasi dalam Pembelajaran Teks Eksposisi Berbasis Discovery Learning dan HOTS - Ella Wulandari; Tressyalina Tressyalina; Bima Mhd Ghaluh (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Text exposition learning is one way to improve students' ability to present ideas and opinions in a structured and clear manner. In text exposition learning, Discovery Learning and HOTS (Higher Order Thinking Skills) are expected to enhance students' ability to present ideas and opinions independently and creatively. Additionally, educational games are also expected to increase students' interest and motivation in learning. Therefore, this research aims to evaluate the implementation of educational games in text exposition learning based on Discovery Learning and HOTS. This research uses qualitative method with case study approach. Data is collected through observation, interview, and document analysis. The results show that the implementation of educational games in text exposition learning based on Discovery Learning and HOTS can increase students' interest and motivation in learning. Students also become more active in learning and are more able to present ideas and opinions independently and creatively. From the results, it can be concluded that the implementation of educational games in text exposition learning based on Discovery Learning and HOTS can enhance the effectiveness of learning.